FRI0172 Commonplace Though not Approved – Monotherapy with Biologics. Data from the Austrian Bioreg Registry. (9th June 2015) - Herold, M.; Eichbauer-Sturm, G.; Puchner, R.; Rintelen, B.; Singer, F.; Leeb, B.
Abstract : Background: The Austrian BioReg registry (http://www.bioreg.at ) was initiated in 2009. Patients treated with one of the nine biologics (abatacept, adalimumab, anakinra, certolizumab, etanercept, golimumab, infliximab, rituximab, tocilizumab) approved in Austria can be included. Patients with ongoing biologic therapy as well as biologic-naïve patients starting biologic therapy can be included. Further documentation is recommended about every six months. Meanwhile, 1493 patients (rheumatoid arthritis (RA) n=857, ankylosing spondylitis (SpA) n=362, psoriatic arthritis (PsA) n=239, treatments out of label n=35) have been documented. Most biologics are approved for treatment of RA only in combination with methotrexate (MTX). Objectives: The aim of this evaluation was to elucidate the percentage of RA patients treated with biologic monotherapy at baseline and at control visits one, two and three years after inclusion in BioReg . Methods: Three different patient groups were defined. Patients with data at baseline and control visit after one or two or three years ±3 months were evaluated for drug therapy at the time of inclusion and at control visit. 411 RA patients with data at baseline and after one year, 186 with data after two years and 98 with data after three years were analyzed. Results: 155/411 had a biologic as monotherapy at baseline, after one year 165/411; 62/186 at baseline, 71/186 after two years; 40/98 at baseline, 43/98 after three years. At baseline 39.7% of patients received a biologic as monotherapy. The percentage of RA patients (40.1; 38.2; 43.9%) on biologic monotherapy seems to increase with time of treatment. Conclusions: About forty percent of RA patients treated with a biologic receive biologics as monotherapy and not in combination with a conventional disease-modifying drug (DMARD). These data are in agreement with observations from other registries (1, 2). References: Emery P et al. Ann Rheum Dis. 2013;72:1897-904 Zhang J et al. Arthritis Care Res 2014 doi: 10.1002/acr.22510 Acknowledgements: BioReg is supported by an unlimited industrial grant. Disclosure of Interest: None declared